Ru-w18o49 gas-sensitive material, gas-sensitive sensor and preparation method thereof

By embedding Ru-W18O49 gas-sensitive material inside a lithium-ion battery, the hydrogen overflow effect of Ru nanoparticles and the lattice oxygen activation mechanism are utilized to solve the problem of hydrogen detection lag in lithium-ion battery thermal runaway early warning. This achieves high sensitivity and rapid response detection of hydrogen, improving the timeliness and safety of early warning.

CN120551382BActive Publication Date: 2025-10-21WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511072687.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-10-21
Estimated Expiration
2045-08-01

AI Technical Summary

Technical Problem

The existing hydrogen detection in lithium-ion battery thermal runaway early warning systems suffers from a lag problem; external sensors cannot capture the initial hydrogen production signal in a timely manner, affecting the effectiveness of thermal runaway early warning.

Method used

Ru-W18O49 gas-sensitive material is embedded in the lithium-ion battery. By loading Ru nanoparticles on the surface of sea urchin-shaped W18O49, the hydrogen overflow effect and lattice oxygen activation mechanism of Ru are utilized to achieve high-sensitivity response and excellent selective detection of hydrogen.

Benefits of technology

It achieves ultra-early detection of hydrogen in an oxygen-free room temperature environment, significantly improving the detection response speed and early warning time, breaking through the technical bottleneck of traditional sensors, and building a self-driven detection system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120551382B_ABST
    Figure CN120551382B_ABST
Patent Text Reader

Abstract

The application provides a Ru-W 18 O 49 gas-sensitive material, a gas-sensitive sensor and a preparation method thereof, and relates to the technical field of gas-sensitive sensor preparation. The gas-sensitive material comprises sea-urchin-shaped W 18 O 49 and Ru nanoparticles loaded on the sea-urchin-shaped W 18 O 49 ; wherein the diameter of the sea-urchin-shaped W 18 O 49 is 0.8-1.2 microns; and the loading amount of the Ru nanoparticles on the surface of the sea-urchin-shaped W 18 O 49 is 1wt%-5wt%. The gas-sensitive sensor prepared based on the Ru-W 18 O 49 gas-sensitive material can be built into a battery system and directly contacts a hydrogen production source, so that the detection response speed is remarkably improved, and the early warning time is advanced to the latent period of thermal runaway.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sensor preparation, in particular to a Ru-W 18 O 49 Gas-sensitive materials, gas-sensitive sensors and methods for preparing the same. Background Art

[0002] As the energy structure shifts toward cleaner and lower-carbon energy sources, lithium-ion batteries (Li-ion batteries) have become a core carrier in fields such as electric vehicles and energy storage power stations due to their high energy density and long lifespan. However, Li-ion batteries present numerous thermal safety issues. Thermal runaway, the most serious safety failure mode for Li-ion batteries, is characterized by irreversibility, intense heat release, and a chain reaction. Thermal runaway is essentially a self-accelerating exothermic process triggered by an imbalance in the battery's internal heat generation and heat dissipation. Research has shown that thermal runaway is accompanied by the release of a large number of characteristic gases, including H2, CO, CO2, and hydrocarbons, with the release sequence closely related to the reaction stage. Among these, hydrogen (H2) is considered the most promising early warning marker due to its initial generation in the early stages of thermal runaway (e.g., during SEI film decomposition), rapid gas generation rate, and high volume fraction (up to 30%-50% of total gas production). Therefore, effective hydrogen detection can promptly detect battery abnormalities in the early stages of thermal runaway, providing a valuable window for implementing appropriate safety measures and preventing further deterioration.

[0003] Metal oxide semiconductor (MOS) sensors offer significant advantages in thermal runaway hydrogen detection: their high sensitivity, high-temperature resistance (capable of withstanding temperatures exceeding 80°C within the battery), low cost, and fast response speed make them a leading choice for practical application. Despite limitations such as the need for heating (200-400°C) and cross-sensitivity, these sensors can be effectively enhanced for interference resistance and stability through nanostructure design (such as porosity), precious metal loading (such as Ru to enhance selectivity), and integrated temperature and humidity compensation algorithms. Compared to the short lifespan and high cost of electrochemical sensors, this technology balances performance and economic benefits, making it particularly suitable for large-scale deployment in electric vehicle battery modules or energy storage systems. It offers a cost-effective solution for early warning of thermal runaway. However, the current mainstream metal oxide semiconductor (MOS) hydrogen sensor detection method places the sensor externally at the battery's pressure relief valve. This external detection approach has the limitation that when hydrogen production reactions occur within the battery, such as electrolyte decomposition, hydrogen must first accumulate to a certain concentration within the battery and then diffuse to the pressure relief valve before being detected by the sensor. This means that even if hydrogen begins to form very early, if its concentration fails to reach the detection threshold during its diffusion to the sensor, there will be a lag in the warning. Such a lag may affect the timely implementation of measures, thereby reducing the effectiveness of preventing thermal runaway.

[0004] Therefore, there is an urgent need to develop a new hydrogen detection method to quickly capture the initial hydrogen production signal, fundamentally breaking through the time and space barriers of traditional external detection. Summary of the Invention

[0005] In view of this, the present invention proposes a Ru-W 18 O 49 Gas-sensitive materials, gas-sensitive sensors, and their preparation methods, by embedding a miniaturized hydrogen sensor inside the battery, overcome the lag problem of existing external detection methods in thermal runaway warning, thereby achieving ultra-early detection of hydrogen and advancing the detection response time to the thermal runaway incubation period, providing a more sufficient time window for battery safety protection.

[0006] The technical solution of the present invention is achieved as follows:

[0007] In a first aspect, the present invention provides a Ru-W 18 O 49 The gas-sensitive material comprises a sea urchin-shaped W 18 O 49 and loaded in the sea urchin-shaped W 18 O 49 Ru nanoparticles on;

[0008] Wherein, the sea urchin-shaped W 18 O 49 The diameter of the Ru nanoparticles is 0.8~1.2μm; the Ru nanoparticles are 18 O 49 The surface loading is 1wt%~5wt%.

[0009] By adopting the above technical solution, in the sea urchin-shaped 18 O 49 The surface is loaded with Ru nanoparticles, and the hydrogen overflow effect of Ru is used to accelerate the dissociative adsorption of H2. The unique lattice oxygen activation mechanism of Ru, that is, the presence of oxygen vacancies is conducive to the formation of Ru-OW, and Ru and W 18 O 49 The strong interaction between them activates the interface lattice oxygen atoms, enabling the sensor to achieve high sensitivity response and excellent selectivity to hydrogen in an oxygen-free room temperature environment, successfully expanding its application in extreme scenarios such as internal battery monitoring and safety warning.

[0010] Furthermore, the Ru nanoparticles are 18 O 49 The surface loading is 2wt%~4wt%.

[0011] By adopting the above technical solution, in the sea urchin-shaped 18 O 49The surface loaded Ru nanoparticles have relatively poor performance due to the small number of active sites provided by 1wt% loading, and some Ru nanoparticles have agglomerated at 5wt% loading, which reduces the number of available active sites and leads to performance degradation. Therefore, the inventors further limit the Ru nanoparticles to the sea urchin-shaped W 18 O 49 The surface loading is 2wt%~4wt%, among which the number of active sites provided by Ru loading reaches a peak at 3wt%.

[0012] S1. Dissolve tungsten chloride in methanol, hydrothermally collect solid product I by centrifugation, and dry it to obtain sea urchin-shaped W 18 O 49 ;

[0013] S2, prepare sea urchin-shaped W 18 O 49 aqueous solution and ruthenium chloride aqueous solution, set aside;

[0014] S3, sea urchin-shaped W 18 O 49 Ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred, and solid product II was collected by centrifugation, dried, and calcined to obtain Ru-W with sea urchin-like structure. 18 O 49 Gas-sensitive materials.

[0015] In step S3 of the present invention, the purpose of calcination is to make the Ru nanoparticles more firmly loaded on the W 18 O 49 surface.

[0016] Furthermore, in step S1, the mass volume ratio of the tungsten chloride to the methanol is 0.125 g to 0.4 g: 40 mL to 80 mL.

[0017] Furthermore, in step S1, the hydrothermal temperature is 160-180° C., and the time is 18-30 hours.

[0018] Furthermore, in step S1, the drying temperature is 60-70° C., and the drying time is 8-12 hours.

[0019] Furthermore, in step S2, the sea urchin-shaped 18 O 49 The mass concentration of the aqueous solution is 2.5-5.0 g / L; the mass concentration of the ruthenium chloride aqueous solution is 0.25-0.5 g / L.

[0020] Further, in step S3, the sea urchin-shaped 18 O 49 The mass ratio of the aqueous solution to the ruthenium chloride aqueous solution is 10:1-5.

[0021] Furthermore, in step S3, the stirring temperature is 20-30° C. and the stirring time is 2 hours. If heating is performed while stirring, the stirring time can be shortened as needed.

[0022] Furthermore, in step S3, the drying temperature is 60-70° C., and the drying time is 10-15 hours.

[0023] Furthermore, in step S3, the calcination temperature is 300° C. and the calcination time is 2 h.

[0024] Furthermore, the calcination temperature is obtained by increasing the drying temperature at a heating rate of 2° C. / min.

[0025] In a third aspect, the present invention provides a gas sensor comprising the Ru-W 18 O 49 The gas-sensitive material is used to detect hydrogen in an oxygen-free environment at a temperature of 20-30°C.

[0026] Furthermore, the gas sensor is used to detect hydrogen in the absence of oxygen and at a temperature of 25±3°C.

[0027] In a fourth aspect, the present invention provides a method for preparing the above-mentioned gas sensor, comprising the following steps: 18 O 49 The gas-sensitive material is mixed with deionized water into a slurry, which is then coated on the surface of a ceramic tube with a gold electrode. After the surface is dried, it is assembled with a Ni-Cr heating wire and a hexagonal base, and then subjected to aging treatment to obtain a gas sensor.

[0028] A Ru-W 18 O 49 The gas-sensitive material, gas-sensitive sensor and preparation method thereof have the following beneficial effects compared with the prior art:

[0029] (1) Ru-W prepared by the present invention 18 O 49 Gas-sensitive materials, by regulating the material morphology and structure, optimize the sea urchin-shaped W 18 O 49 The spatial distribution of surface active sites (oxygen vacancies) enables Ru elements to be more evenly anchored on W 18 O 49 On the surface, this significantly improves the material's response performance and sensitivity to hydrogen, and further enhances its gas-sensing properties at room temperature and in an oxygen-free environment.

[0030] (2) The present invention is based on Ru-W 18 O 49Gas sensors made of gas-sensitive materials can be built into the battery system and directly contact the source of hydrogen production, which significantly improves the detection response speed and advances the warning time to the latent period of thermal runaway.

[0031] (3) The gas sensor of the present invention exhibits excellent hydrogen sensitivity even in an oxygen-free environment. Furthermore, it successfully achieves a rapid response to ppm-level hydrogen at room temperature, breaking through the technical bottleneck of traditional metal oxide sensors that require heating or ultraviolet irradiation, and constructing a self-powered detection system that does not require external energy supply. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 These are scanning electron microscope images of gas-sensitive materials prepared in Example 4, Examples 7-8, and Comparative Example 3 of the present invention; in the figures, (a) is a scanning electron microscope image of Comparative Example 3, (b) is a scanning electron microscope image of Example 7, (c) is a scanning electron microscope image of Example 4, and (d) is a scanning electron microscope image of Example 8;

[0034] Figure 2 X-ray diffraction patterns of gas-sensitive materials prepared in Examples 1 to 4, Examples 7 to 8, and Comparative Examples 1 to 3 of the present invention; in the figure, (a) is the X-ray diffraction pattern of Examples 1 to 3 and Comparative Examples 1 to 2, and (b) is the X-ray diffraction pattern of Example 4, Examples 7 to 8, and Comparative Example 3;

[0035] Figure 3 This is the EDS mapping diagram of the gas-sensitive material prepared in Example 9 of the present invention;

[0036] Figure 4 Graph showing changes in resistance over time of the gas sensors prepared in Examples 4 to 8 of the present invention and Comparative Example 3;

[0037] Figure 5 This is a comparison chart of the response values ​​of the gas sensors prepared in Example 4 of the present invention and Comparative Example 3 to different gases under the same test conditions;

[0038] Figure 6 This is a comparison chart of the response values ​​of the gas sensors prepared in Example 4 of the present invention and Comparative Example 4 to different concentrations of hydrogen under the same test conditions. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0040] Based on the warning lag problem of external sensor design, the inventors proposed an in-situ embedded hydrogen monitoring solution: by embedding a miniaturized hydrogen sensor inside the battery, the initial hydrogen production signal can be captured in situ to improve the timeliness and accuracy of detection.

[0041] However, the sensor used for hydrogen detection inside the battery must meet the following key technical requirements: First, the sensor must have the ability to efficiently detect hydrogen at room temperature. 18 O 49 Gas-sensitive materials optimize the spatial distribution of surface active sites (oxygen vacancies) by regulating the material morphology and structure, making the Ru element more evenly anchored on the W 18 O 49 On the surface, this further enhances its hydrogen sensing performance. Secondly, the interior of the battery is typically oxygen-free. Even if a small amount of oxygen is produced during thermal runaway, it will be quickly consumed by other side reactions. Therefore, the sensor must be able to operate stably in oxygen-free conditions to effectively detect hydrogen.

[0042] The inventors found in practice that traditional metal oxide sensors rely on the "adsorption-desorption" mechanism of surface oxygen, that is, oxygen molecules form O on the surface of the material through chemical adsorption. - Active oxygen species such as HO react with hydrogen molecules, namely H2+O - → H2O + e - However, in an oxygen-free environment, this mechanism completely fails, severely limiting its application within batteries.

[0043] The inventors made the present invention through further experiments and exploration. Based on the oxygen vacancy engineering control strategy, the inventors selected W rich in oxygen vacancies. 18 O 49 Material as substrate, W 18 O 49 It is a non-stoichiometric n-type semiconductor metal oxide with abundant oxygen defects and high specific surface area. On the one hand, its unique electronic structure (W 5+ / W 6+Mixed valence state) and a large number of surface active sites, showing excellent adsorption and catalytic conversion ability for hydrogen. On the other hand, its oxygen vacancies can serve as precious metal anchoring sites and electron transmission channels, significantly enhancing the dissociation efficiency of hydrogen molecules. Therefore, the inventors further considered the 18 O 49 The surface is loaded with the precious metal Ru, which activates lattice oxygen through its catalytic sensitization, creating a novel hydrogen sensing mechanism suitable for room temperature and oxygen-free environments. This mechanism not only achieves high sensitivity and rapid response to hydrogen detection, but also provides key technical support for improving the timeliness of thermal runaway warnings and ensuring the overall safety of power battery systems.

[0044] The present invention will be further described below with reference to specific examples, but the scope of protection of the present invention is not limited by the following examples. Unless otherwise specified, the materials mainly involved in the following examples are conventional commercial products.

[0045] Example 1

[0046] This embodiment provides a Ru-W 18 O 49 The gas-sensitive material is prepared by the following steps:

[0047] S1. Dissolve 0.4 g of tungsten chloride in 80 mL of methanol at 25 °C with stirring. After dissolution, hydroheat at 180 °C for 24 h, then centrifuge at 8000 r / min for 5 min, collect the precipitate, wash the precipitate with deionized water for at least 4 times, and dry the collected solid product I at 60 °C for 10 h to obtain sea urchin-shaped tungsten chloride. 18 O 49 Material;

[0048] Step S1: Preparation of sea urchin-shaped W 18 O 49 The reaction mechanism of the material is as follows:

[0049] ①WCl6+ CH3OH → CH3OWCl5+ HCl;

[0050] ②CH3OH + CH3OH → CH3OCH3+ H2O;

[0051] ③CH3OWCl5+ H2O → WO 3-x + CH3OH + HCl;

[0052] S2, take 0.2g of sea urchin-shaped W prepared in S1 18 O 49 The material was stirred and dissolved in 40 mL of deionized water to prepare sea urchin-shaped W 18 O 49 Aqueous solution, set aside;

[0053] Prepare a 0.5 mg / mL ruthenium chloride aqueous solution by dissolving 0.03 g of RuCl3·xH2O (Aladdin, 35-42% Ru, R109234-1 g) in 60 mL of deionized water. (Note: The ruthenium chloride aqueous solution must be prepared and used immediately, and stored in the dark to prevent deterioration.)

[0054] S3, sea urchin-shaped W towards S2 18 O 49 12 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 25 ° C for 2 h, and then centrifuged at 8000 r / min for 5 min. The precipitate was collected and washed with deionized water at least 4 times. The collected solid product II was dried at 60 ° C for 10 h, and then heated to 300 ° C at a rate of 2 ° C / min in a muffle furnace and calcined for 2 h to obtain Ru-W with a sea urchin-like structure. 18 O 49 Gas-sensitive material, denoted as W-1;

[0055] In this embodiment, the Ru nanoparticles are 18 O 49 The surface loading was 3 wt%.

[0056] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (a) in .

[0057] Example 2

[0058] The difference from Example 1 is that: S1, 0.4g of tungsten chloride was dissolved in 80mL of methanol at 25°C with stirring, and after dissolution, it was hydrothermaled at 180°C for 18h, and then centrifuged at 8000r / min for 5min, and the precipitate was collected. After washing the precipitate with deionized water at least 4 times, the collected solid product I was dried at a constant temperature of 60°C for 10h to obtain sea urchin-shaped tungsten. 18 O 49 Materials; other conditions remain unchanged and are recorded as W-2.

[0059] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (a) in .

[0060] Example 3

[0061] The difference from Example 1 is that: S1, 0.4g of tungsten chloride was dissolved in 80mL of methanol at 25°C with stirring, and after dissolution, it was hydrothermaled at 180°C for 30h, and then centrifuged at 8000r / min for 5min, and the precipitate was collected. After washing the precipitate with deionized water at least 4 times, the collected solid product I was dried at a constant temperature of 60°C for 10h to obtain sea urchin-shaped tungsten. 18 O 49 Materials; other conditions remain unchanged and are recorded as W-3.

[0062] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (a) in .

[0063] Comparative Example 1

[0064] The difference from Example 1 is that: S1, 0.4g of tungsten chloride was dissolved in 80mL of methanol at 25°C with stirring, and after dissolution, it was hydrothermaled at 180°C for 12h, and then centrifuged at 8000r / min for 5min, and the precipitate was collected. After washing the precipitate with deionized water at least 4 times, the collected solid product I was dried at a constant temperature of 60°C for 10h to obtain sea urchin-shaped tungsten chloride. 18 O 49 Materials; other conditions remain unchanged and are recorded as D-1.

[0065] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (a) in .

[0066] Comparative Example 2

[0067] The difference from Example 1 is that: S1, 0.4g of tungsten chloride was dissolved in 80mL of methanol at 25°C with stirring, and after dissolution, it was hydrothermaled at 180°C for 36h, and then centrifuged at 8000r / min for 5min, and the precipitate was collected. After washing the precipitate with deionized water at least 4 times, the collected solid product I was dried at a constant temperature of 60°C for 10h to obtain sea urchin-shaped tungsten. 18 O 49 Materials; other conditions remain unchanged and are recorded as D-2.

[0068] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (a) in .

[0069] pass Figure 2(a) Analysis of Examples 1 to 3 and Comparative Examples 1 to 2 shows that: with the extension of the hydrothermal time, the morphological evolution of the sea urchin-like nanoparticles shows obvious stages: the 12-hour hydrothermal reaction can only preliminarily induce the formation of some sea urchin-like nanoparticles, and the corresponding XRD characteristic peak broadens; after 18 hours, the product basically presents a sea urchin-like morphology, but the particle size distribution is wide and the uniformity is poor, the corresponding XRD characteristic peak intensity is low, and the crystallinity is poor; after 24 hours, the particle morphology tends to be uniform, the sea urchin-like structure is fully developed and the size distribution is significantly narrowed, the corresponding XRD characteristic peak intensity is high, and the crystallinity is good; after 30 hours, the particles grow significantly (Ostwald ripening effect appears), the corresponding XRD characteristic peak intensity is high, the crystallinity is good, but the grain size is too large, which is not conducive to gas sensing performance; and when extended to 36 hours, the local particle structure collapses, and the corresponding XRD characteristic peak intensity decreases.

[0070] Example 4

[0071] This embodiment provides a Ru-W 18 O 49 The gas-sensitive material is prepared by the following steps:

[0072] S1. Dissolve 0.125 g of tungsten chloride in 40 mL of methanol at 22 °C with stirring. After dissolution, hydroheat at 160 °C for 24 h, then centrifuge at 8000 r / min for 5 min, collect the precipitate, wash the precipitate with deionized water at least 4 times, and dry the collected solid product I at 70 °C for 8 h to obtain sea urchin-shaped tungsten. 18 O 49 Material;

[0073] S2, take 0.2g of sea urchin-shaped W prepared in S1 18 O 49 The material was stirred and dissolved in 40 mL of deionized water to prepare sea urchin-shaped W 18 O 49 Aqueous solution, set aside;

[0074] Prepare a 0.5 mg / mL ruthenium chloride aqueous solution for later use (same as in Example 1);

[0075] S3, sea urchin-shaped W towards S2 18 O 49 12 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 22 ° C for 2 h, and centrifuged at 8000 r / min for 5 min. The solid product II was collected and dried at 60 ° C for 12 h. Then, the temperature was increased to 300 ° C at a rate of 2 ° C / min and calcined for 2 h to obtain Ru-W with a sea urchin-like structure. 18 O 49 Gas-sensitive material, denoted as W-4;

[0076] In this embodiment, the Ru nanoparticles are 18 O 49 The surface loading was 3 wt%.

[0077] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials were analyzed by scanning electron microscopy, such as Figure 1 As shown in (c) in the figure.

[0078] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (b) in .

[0079] Example 5

[0080] The difference from Example 4 is that: S3, the sea urchin-shaped W to S2 18 O 49 8 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 22 ° C for 2 h, and centrifuged at 8000 r / min for 5 min. The solid product II was collected and dried at 60 ° C for 12 h. Then, the temperature was raised to 300 ° C at a rate of 2 ° C / min and calcined for 2 h to obtain Ru-W with a sea urchin-like structure. 18 O 49 The gas-sensitive material is denoted as W-5; the other conditions remain unchanged.

[0081] In this embodiment, the Ru nanoparticles are 18 O 49 The surface loading was 2 wt%.

[0082] Example 6

[0083] The difference from Example 4 is that: S3, the sea urchin-shaped W to S2 18 O 49 16 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 22 ° C for 2 h, and centrifuged at 8000 r / min for 5 min. The solid product II was collected and dried at 60 ° C for 12 h. Then, the temperature was raised to 300 ° C at a rate of 2 ° C / min and calcined for 2 h to obtain Ru-W with a sea urchin-like structure. 18 O 49 The gas-sensitive material is denoted as W-6; the other conditions remain unchanged.

[0084] In this embodiment, the Ru nanoparticles are 18 O 49 The surface loading was 4 wt%.

[0085] Example 7

[0086] The difference from Example 4 is that: S3, the sea urchin-shaped W to S2 18 O 49 4 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution while other conditions remained unchanged, which was recorded as W-7.

[0087] In this embodiment, the Ru nanoparticles are 18 O 49 The surface loading was 1 wt%.

[0088] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials were analyzed by scanning electron microscopy, such as Figure 1 As shown in (b) in .

[0089] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (b) in .

[0090] Example 8

[0091] The difference from Example 4 is that: S3, the sea urchin-shaped W to S2 18 O 49 20 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution while other conditions remained unchanged, which was recorded as W-8.

[0092] In this embodiment, the Ru nanoparticles are 18 O 49 The surface loading was 5 wt%.

[0093] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials were analyzed by scanning electron microscopy, such as Figure 1 As shown in (d) in the figure.

[0094] The Ru-W of the sea urchin-like structure prepared in this embodiment 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (b) in .

[0095] Comparative Example 3

[0096] The difference from Example 4 is that: no sea urchin-shaped W 18 O 49 The surface is loaded with Ru nanoparticles, the preparation steps are adjusted adaptively, and the other conditions remain unchanged. The final product is sea urchin-shaped W 18O 49 Material, recorded as D-3.

[0097] The sea urchin-shaped W prepared in this comparative example 18 O 49 Gas-sensitive materials were analyzed by scanning electron microscopy, such as Figure 1 As shown in (a) in .

[0098] The sea urchin-shaped W prepared in this comparative example 18 O 49 Gas-sensitive materials are subjected to X-ray diffraction analysis, such as Figure 2 As shown in (b) in .

[0099] Combine Figure 1 From (a) to (d) in the figure, we can see that: the sample (a) corresponding to D-3 is in the shape of a sea urchin, with a particle size of about 1 μm; the sample (b) corresponding to W-7 has shorter sea urchin whiskers and is wrapped by several small particles; the sample (c) corresponding to W-4 has shorter sea urchin whiskers and is wrapped by more small particles. The surface has changed significantly compared to W-7, but the morphology is still in the shape of a sea urchin; the sample (d) corresponding to W-8 has almost no sea urchin whiskers, and the small particles have agglomerated on the surface. This shows that Ru is well loaded on W 18 O 49 The surface of the material, and with the increase of Ru loading, the passivation of sea urchin whiskers becomes more and more serious, and the specific surface area of ​​the corresponding material is decreasing, resulting in a decrease in active sites, but with the increase of Ru loading, the active sites are increasing. When 3wt% Ru is added, the two reach a balance point, and the number of active sites reaches the maximum value.

[0100] Combine Figure 2 From (a) and (b) in the figure, we can see that clear diffraction peaks were observed for all samples, and they were consistent with W 18 O 49 The standard card (PDF#71-2450) matches, indicating that the sample has a very high purity. There is no characteristic diffraction peak related to Ru in the spectrum, which may be due to the Ru substance in W 18 O 49 This is related to the low loading amount on the carrier and the high dispersion.

[0101] Example 9

[0102] This embodiment provides a Ru-W 18 O 49 The gas-sensitive material is prepared by the following steps:

[0103] S1. Dissolve 0.26 g of tungsten chloride in 60 mL of methanol at 28 ° C with stirring. After dissolution, hydroheat at 170 ° C for 24 h, then centrifuge at 8000 r / min for 5 min, collect the precipitate, wash the precipitate with deionized water at least 4 times, and dry the collected solid product I at 65 ° C for 12 h to obtain sea urchin-shaped tungsten. 18 O 49 Material;

[0104] S2, take 0.1g of sea urchin-shaped W prepared in S1 18 O 49 The material was stirred and dissolved in 40 mL of deionized water to prepare sea urchin-shaped W 18 O 49 Aqueous solution, set aside;

[0105] Prepare a 0.4 mg / mL ruthenium chloride aqueous solution for later use;

[0106] S3, sea urchin-shaped W towards S2 18 O 49 12 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 28 ° C for 2 h, and centrifuged at 8000 r / min for 5 min. The solid product II was collected and dried at 65 ° C for 8 h. Then, the temperature was raised to 300 ° C at a rate of 2 ° C / min and calcined for 2 h to obtain Ru-W with a sea urchin-like structure. 18 O 49 Gas-sensitive material, denoted as W-9.

[0107] The Ru-W sea urchin-like structure prepared in this example 18 O 49 The gas-sensitive material was subjected to EDS mapping image analysis, and the results were as follows: Figure 3 shown.

[0108] Depend on Figure 3 It can be seen that the existence of Ru element is confirmed, and Ru nanoparticles are evenly distributed in the sea urchin-shaped W 18 O 49 On the surface of the material.

[0109] Example 10

[0110] This embodiment provides a Ru-W 18 O 49 The gas-sensitive material is prepared by the following steps:

[0111] S1. Dissolve 0.27 g of tungsten chloride in 60 mL of methanol at 22°C with stirring. After dissolution, hydroheat at 160°C for 24 h, then centrifuge at 8000 r / min for 5 min, collect the precipitate, wash the precipitate with deionized water at least 4 times, and dry the collected solid product I at 70°C for 8 h to obtain sea urchin-shaped tungsten.18 O 49 Material;

[0112] S2, take 0.15g of sea urchin-shaped W prepared in S1 18 O 49 The material was stirred and dissolved in 40 mL of deionized water to prepare sea urchin-shaped W 18 O 49 Aqueous solution, set aside;

[0113] Prepare a 0.25 mg / mL ruthenium chloride aqueous solution for later use;

[0114] S3, sea urchin-shaped W towards S2 18 O 49 12 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 22 ° C for 2 h, and centrifuged at 8000 r / min for 5 min to collect the solid product II, which was dried at 70 ° C in a vacuum drying oven for 12 h, and then heated to 300 ° C in a muffle furnace at a rate of 2 ° C / min and calcined for 2 h to obtain Ru-W with a sea urchin-like structure. 18 O 49 Gas-sensitive material, denoted as W-10.

[0115] Example 11

[0116] This embodiment provides a Ru-W 18 O 49 The gas-sensitive material is prepared by the following steps:

[0117] S1. Dissolve 0.26 g of tungsten chloride in 60 mL of methanol at 28 ° C with stirring. After dissolution, hydroheat at 170 ° C for 24 h, then centrifuge at 8000 r / min for 5 min, collect the precipitate, wash the precipitate with deionized water at least 4 times, and dry the collected solid product I at 65 ° C for 12 h to obtain sea urchin-shaped tungsten. 18 O 49 Material;

[0118] S2, take 0.1g of sea urchin-shaped W prepared in S1 18 O 49 The material was stirred and dissolved in 40 mL of deionized water to prepare sea urchin-shaped W 18 O 49 Aqueous solution, set aside;

[0119] Prepare a 0.3 mg / mL ruthenium chloride aqueous solution for later use;

[0120] S3, sea urchin-shaped W towards S2 18 O 4912 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 28 ° C for 2 h, and centrifuged at 8000 r / min for 5 min. The solid product II was collected and dried at 65 ° C for 8 h. Then, the temperature was raised to 300 ° C at a rate of 2 ° C / min and calcined for 2 h to obtain Ru-W with a sea urchin-like structure. 18 O 49 Gas-sensitive material, denoted as W-11.

[0121] Comparative Example 4

[0122] This comparative example provides a spherical shell Ru-W 18 O 49 The gas-sensitive material is prepared by the following steps:

[0123] S1: 0.24 g of tungsten chloride was dissolved in 80 mL of acetic acid at 25 °C with stirring. After dissolution, it was hydrothermaled at 180 °C for 16 h, and then centrifuged at 8000 r / min for 5 min. The precipitate was collected and washed alternately with deionized water and ethanol for at least 4 times. The collected solid product I was dried at 60 °C for 10 h to obtain spherical shell W 18 O 49 Material

[0124] S2, take 0.2g of spherical shell W prepared by S1 18 O 49 The material was stirred and dissolved in 40 mL of deionized water to prepare spherical shell W 18 O 49 Aqueous solution, set aside;

[0125] Prepare a 0.5 mg / mL ruthenium chloride aqueous solution for later use;

[0126] S3, spherical shell W towards S2 18 O 49 12 mL of ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred at 25 ° C for 2 h, and centrifuged at 8000 r / min for 5 min to collect the solid product II, dried at 70 ° C for 10 h, and then heated to 300 ° C at a rate of 2 ° C / min and calcined at this temperature for 2 h to obtain Ru-W with a spherical shell structure. 18 O 49 Gas-sensitive material, denoted as D-4.

[0127] In this embodiment, the Ru nanoparticles are 18 O 49 The surface loading was 3 wt%.

[0128] The gas sensor is prepared by using the gas-sensitive materials prepared in the above embodiment and comparative example, comprising the following steps:

[0129] Take 6 mg of gas-sensitive material, grind it with deionized water in an agate mortar and mix it evenly to form a slurry. Use a fine-bristled brush to dip the slurry and apply it to a ceramic tube with a gold electrode so that it completely covers the gold electrode. Then dry it at room temperature. Use tin and solder paste to weld the four platinum wires and the two ends of the heating wire of the ceramic tube to the six pin sockets of the base. Place it on the aging table of the gas-sensitive component test system and age it in an air environment at 200°C for three days to make a gas sensor.

[0130] The gas-sensing performance test uses the WS-30B gas-sensing test system from Zhengzhou Weisheng Technology Co., Ltd., combined with a sealed container designed independently by the laboratory to create a test environment, ensuring that the entire experimental process is carried out in a static test mode at room temperature and in an oxygen-free (nitrogen atmosphere). The specific process is as follows: First, start the test program and set the operating voltage. High-purity nitrogen gas is continuously introduced to replace the residual gas in the test chamber. The nitrogen introduction is terminated after the sensor baseline resistance (Ra) stabilizes. The target gas is then quantitatively injected through a trace gas syringe, and the response resistance value (Rg) of the sensor in the mixed atmosphere is recorded in real time. After completing a single test, nitrogen gas is reintroduced and the test is terminated after the resistance value returns to the initial baseline level. The response value is defined as S=Ra / Rg (reducing gas H2).

[0131] The gas-sensing test results are shown in Table 1 and Figure 4 shown.

[0132] Table 1 Performance test results

[0133]

[0134] Combined with Table 1 and Figure 4 It can be seen that: W without Ru load 18 O 49 At room temperature and in the absence of oxygen, the gas-sensing performance showed little response to 100 ppm hydrogen (the concentration simulating the thermal runaway incubation period). The gas-sensing performance first increased and then decreased with increasing loading, primarily because a lower loading provided fewer active sites. Excessive loading led to particle agglomeration, which degraded the gas-sensing performance. 3wt% showed the best gas-sensing performance, with a response value of 3.96 to 100 ppm hydrogen.

[0135] The gas sensor prepared by the gas-sensitive material of Example 4 was tested for response to 100 ppm of five target gases (hydrogen, carbon monoxide, methane, carbon dioxide, and ethylene) under oxygen-free room temperature. Figure 5 shown.

[0136] Depend on Figure 5 It can be seen that the Ru-W-based 18 O 49Gas sensors made of gas-sensitive materials have excellent selectivity for hydrogen among several main gases produced by thermal runaway of lithium-ion batteries.

[0137] The gas sensor prepared by the gas-sensitive material of Example 4 and Comparative Example 4 was tested for response to 25-500 ppm hydrogen at room temperature without oxygen. Figure 6 shown.

[0138] Depend on Figure 6 It can be seen that: sea urchin-shaped Ru-W 18 O 49 The gas-sensitive response to hydrogen is significantly better than that of spherical shell Ru-W 18 O 49 .

[0139] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An application of a gas sensor for detecting hydrogen in the absence of oxygen and at a temperature of 20-30°C, characterized in that: The gas sensor includes Ru-W 18 O 49 Gas-sensitive material, the Ru-W 18 O 49 Gas-sensitive materials include sea urchin-shaped W 18 O 49 and loaded in the sea urchin-shaped W 18 O 49 Ru nanoparticles on; Wherein, the sea urchin-shaped W 18 O 49 The diameter of the Ru nanoparticles is 0.8~1.2μm; the Ru nanoparticles are 18 O 49 The surface loading is 2wt%~4wt%.

2. The use according to claim 1, characterized in that The Ru-W 18 O 49 The preparation method of the gas-sensitive material comprises the following steps: S1. Dissolve tungsten chloride in methanol, hydrothermal, centrifuge and wash to collect solid product I, dry it, and obtain sea urchin-shaped W 18 O 49 ; S2, prepare sea urchin-shaped W 18 O 49 aqueous solution and ruthenium chloride aqueous solution, set aside; S3, sea urchin-shaped W 18 O 49 Ruthenium chloride aqueous solution was added dropwise to the aqueous solution, stirred, centrifuged and washed to collect the solid product II, dried, and calcined to obtain Ru-W with sea urchin-like structure. 18 O 49 Gas-sensitive materials.

3. The use according to claim 2, characterized in that In step S1, the mass volume ratio of the tungsten chloride to the methanol is 0.125 g to 0.4 g: 40 mL to 80 mL.

4. The use according to claim 3, characterized in that In step S1, the hydrothermal temperature is 160-180° C., and the time is 18-30 hours; the drying temperature is 60-70° C., and the time is 8-12 hours.

5. The use according to claim 2, characterized in that In step S2, the sea urchin-shaped 18 O 49 The mass concentration of the aqueous solution is 2.5-5.0 g / L; the mass concentration of the ruthenium chloride aqueous solution is 0.25-0.5 g / L.

6. The use according to claim 2, characterized in that In step S3, the sea urchin-shaped 18 O 49 The mass ratio of the aqueous solution to the ruthenium chloride aqueous solution is 10:1-5.

7. The use according to claim 6, characterized in that In step S3, the stirring temperature is 20-30° C. and the time is 2 h; the drying temperature is 60-70° C. and the time is 10-15 h; and the calcination temperature is 300° C. and the time is 2 h.

8. The use according to claim 1, wherein The preparation method of the gas sensor comprises the following steps: The Ru-W 18 O 49 The gas-sensitive material is mixed with deionized water to form a slurry, which is then coated on the surface of an Al2O3 ceramic tube with a gold electrode. After the surface is dried, it is assembled with a Ni-Cr heating wire and a hexagonal base, and then subjected to aging treatment to obtain a gas sensor.

Citation Information

Patent Citations

  • Preparation method of Pd / W18O49 composite material for improving performance of hydrogen sensors

    CN107966479A

  • Preparation method of n-nonanal volatile gas sensitive material

    CN113173602A